Podcast Sebagai Media Alternatif Praktik Jurnalistik Radio oleh Tempo - Muslimah, Fauziah (Faculty of Da'wa and Communications Sciences, 2022)
The presence of podcasts is a form of development of radio journalism practice in the era of convergence. This article discusses three podcast programs on Tempo media: Berita Utama Koran Tempo, Apa Kabar Tempo, and Celetuk Bahasa Tempo. This article uses a qualitative approach to examine how the play on-demand aspect as one of a podcast's characteristics works in radio journalism practices. The results show that three Tempo podcast content applies content production practices that cannot be separated from the character of radio media, such as auditive, emphasizing conversation, at a glance, and global. The article also shows that although podcasts come with the concept of play on-demand that allows listeners to re-listen to old episodes, podcasts have not succeeded in building interaction between the mass media and their listeners. Thus, interactivity as one of the characteristics of radio journalism has not been fully present in this podcast.